Analysis of the Implementation of Law Number 4 of 2009 concerning Mineral and Coal Mining, Tax Relevance: Through a Literature Review - Antonius; Al-Anshori, Huzaimah; Hasibuan, Ali Huristak Hartawan (Universitas Islam Negeri Alauddin Makassar, 2025)
Indonesia’s mineral and coal mining sector continues to face persistent governance challenges, including regulatory inconsistency, limited transparency, and weak fiscal accountability. Although Law Number 4 of 2009—introducing the IUP/IUPK licensing system—was intended to strengthen state control and promote sustainable resource management, its practical outcomes remain inconsistent. Addressing the research gap on how legal reforms interact with fiscal governance, this study analyzes the implementation of the law and its taxation relevance through a systematic literature review of academic publications, official reports, and regulatory documents. Using a qualitative content analysis approach, the study identifies recurring issues such as overlapping regulations, legal uncertainty, and insufficient supervision, which undermine the expected improvements in mining governance. The results also show that the mining taxation framework—comprising income tax, VAT, land and building tax, non-tax state revenues (PNBP), and the Revenue Sharing Fund (DBH)—holds strategic importance for ensuring equitable fiscal distribution, yet suffers from low compliance and weak monitoring mechanisms. The study contributes to existing scholarship by demonstrating that effective mining governance requires not only legal reform but also coherent fiscal policy design and integrated regulatory enforcement. Practically, these findings suggest that enhancing regulatory harmonization, strengthening fiscal transparency, and improving intergovernmental coordination are essential to optimizing state revenue and ensuring that the mining sector supports long-term sustainable development.